Projeto e Análise de uma Classe de Antenas Refletoras para Cobertura Ommidirecional - Bergmann, J. R.; Hasselmann, F. J. V.; Branco, M. G. C. (Journal of Communication and Information Systems, 2018)
A single reflector antenna design is suggested for compliance with omnidirectional azimuth coverage requirements in radio base stations for point-to-multipoint services at millimetric bands. Free-space attenuation between transmitter and receiver ends is accounted for by properly shaping the reflector profile to yield a cosecant squared power pattern in the vertical plane. Numerical results illustrate the trade-offs involved when considering certain antenna design aspects as well as feed requirements. The role of both Geometrical and Physical Optics is carefully explored along design and analysis steps with a view towards guiding the reader through key factors of this study in an appropriate sequence. The importance of proper modelling of feed patterns is also evidenced